Relationship between pregnant women's compliance in consuming iron tablets with hemoglobin levels - Sumiati, Sumiati; Nanda, Nanda; Putri, Refalina Dwi Sagita; Anitasari, Bestfy (Indonesian Institute for Counseling, Education and Therapy (IICET), 2025)
This study explores the relationship between pregnant women's compliance in consuming iron tablets and their hemoglobin levels, focusing on evidence from previous qualitative studies and literature reviews. Iron supplementation is a critical intervention for preventing anemia during pregnancy, which is a major public health concern worldwide, including in Indonesia. Non-compliance in iron tablet consumption is often linked to various factors such as side effects, lack of knowledge, cultural beliefs, and accessibility issues. Through a qualitative literature review approach, this study synthesizes findings from multiple scholarly articles, reports, and case studies to identify patterns, barriers, and facilitators affecting compliance among pregnant women. The review highlights that adherence to iron supplementation positively correlates with improved hemoglobin levels, which is essential for maternal and fetal health. It also underscores the importance of health education, counseling, and community support in enhancing compliance rates. Cultural sensitivity and tailored interventions are critical to addressing misconceptions and improving iron tablet intake. Furthermore, the study discusses the role of healthcare providers and community health centers, such as Pontap Palopo Community Health Center, in monitoring and promoting adherence to iron supplementation programs. The findings suggest that improving compliance requires a multifaceted approach combining education, accessibility, and supportive healthcare systems. This review provides valuable insights for public health practitioners and policymakers aiming to design effective strategies to combat anemia in pregnancy by improving iron tablet compliance. Future research should consider more localized qualitative studies to understand specific community dynamics influencing compliance behaviors.